Early histological changes in the porcine aortic media after thoracic stent-graft implantation - Scheumann, Johannes; Böckler, Dittmar; Bischoff, Moritz (Journal of endovascular therapy, 2012)
Purpose: To describe the histological findings in the aortic wall 5 days after thoracic endovascular aortic repair (TEVAR) in a porcine model., Methods: Two overlapping stent-grafts were implanted in each of 6 juvenile pigs, covering the entire descending thoracic aorta (DTA). On the 5th postoperative day, tissue samples were taken from the DTA in each animal. Medial thickness and medial necrosis were quantified and compared to measurements from the aortas of 6 control animals., Results: Significant medial thinning was observed in stent-covered regions in the test animals. At the proximal landing zone, aortic wall thickness changed from 1387±68 to 782±74 µm within the covered aortic segment (p=0.028); at the distal landing site, the wall thickness was 365±67 µm within the stent and 501±57 µm distally (p=0.028). In the overlap zone, the aortic wall measured 524±122 vs. 1053±77 µm in native controls (p=0.004). Aortic thickness proximal to the graft did not differ from the proximal region of native aortas (1468±96 vs. 1513±80 µm, p=0.423), but the aorta was significantly thinner distal to the stent (707±38 vs. 815±52 µm, p=0.004). Laminar necrosis constituted 38%±7% of the media in the proximal landing zone, 54%±4% in the overlap zone, and 46%±13% in the distal landing zone., Conclusion: In this porcine model, significant medial thinning and necrosis of the stented aorta was observed. The findings suggest an early phase of vulnerability of the aortic wall, before scarring and adaptive changes have strengthened the residual aorta.